Affinity-controlled capture and release of engineered monoclonal antibodies by macroporous dextran hydrogels using coiled-coil interactions - Seyed Farzad Baniahmad; Romane Oliverio; Ines Obregon-Gomez; Alma Robert; Anne E.G. Lenferink; Elena Pazos; Nick Virgilio; Xavier Banquy; Gregory De Crescenzo; Yves Durocher (Taylor & Francis Group, 2023)
ABSTRACTLong-term delivery is a successful strategy used to reduce the adverse effects of monoclonal antibody (mAb)-based treatments. Macroporous hydrogels and affinity-based strategies have shown promising results in sustained and localized delivery of the mAbs. Among the potential tools for affinity-based delivery systems, the de novo designed Ecoil and Kcoil peptides are engineered to form a high-affinity, heterodimeric coiled-coil complex under physiological conditions. In this study, we created a set of trastuzumab molecules tagged with various Ecoil peptides and evaluated their manufacturability and characteristics. Our data show that addition of an Ecoil tag at the C-termini of the antibody chains (light chains, heavy chains, or both) does not hinder the production of chimeric trastuzumab in CHO cells or affect antibody binding to its antigen. We also evaluated the influence of the number, length, and position of the Ecoil tags on the capture and release of Ecoil-tagged trastuzumab from macroporous dextran hydrogels functionalized with Kcoil peptide (the Ecoil peptide-binding partner). Notably, our data show that antibodies are released from the macroporous hydrogels in a biphasic manner; the first phase corresponding to the rapid release of residual, unbound trastuzumab from the macropores, followed by the affinity-controlled, slow-rate release of antibodies from the Kcoil-functionalized macropore surface.